2014
DOI: 10.7243/2052-434x-2-2
|View full text |Cite
|
Sign up to set email alerts
|

First recorded case of haemoglobin SC in sudan

Abstract: A haemoglobin (Hb) disorder was the first polymorphism suggested to have a relationship with malaria, as Hb S and C offer a survival advantage in malarial endemic regions. Two schoolgirls aged 11 and 16 were admitted to the Military Hospital in Omdurman on the 2 nd of April 2009. They had Hb (haemoglobin) SC and their parents were carriers of abnormal Hb; the mother was (HbAS) and father (HbAC). These girls were the first reported cases of HbSC in Sudan. Capillary Electrophoresis (CE) was initially used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…According to Bain, the prevalence of HbS, HbC and β-thalassemia in Sudan is 1-17%, 0%, and 1-10% (overall prevalence: 4%), respectively (11). However, Elderdery et al reported two cases with HbSC in Sudan (11,12). They also reported the S gene as the most common variant among the Western tribes (12%) and the general Sudanese population (6.1%) (13).…”
Section: Discussionmentioning
confidence: 99%
“…According to Bain, the prevalence of HbS, HbC and β-thalassemia in Sudan is 1-17%, 0%, and 1-10% (overall prevalence: 4%), respectively (11). However, Elderdery et al reported two cases with HbSC in Sudan (11,12). They also reported the S gene as the most common variant among the Western tribes (12%) and the general Sudanese population (6.1%) (13).…”
Section: Discussionmentioning
confidence: 99%